Employ Computer Technology (Power Point( For Development of Technical Skills for Students of Education Technical Material in Colors: اخلاص هاشم عودة (Al-Academy, 2016)
Resulted in scientific and technological developments to the emergence of changes in the educational process and methods of teaching modern formats commensurate with the level of mental retardation. Which called for educational institutions, including the University of Baghdad / College of Fine Arts to urge and guide researchers to study and follow-up of recent developments in the educational process in order to develop in the fine arts in general and technical education in particular being play an important role in achieving educational goals. The educational methods of modern educational require effort-intensive and advanced for the development of technical skills among students, and thus worked researcher to employ computer technology (power point) for the development of technical skills for students of art education in the subject of colors, and through the development of training programs, educational the task of development of technical skills among students. So is being search of the first quarter, which included the research problem the researcher has conducted a prospective study on a sample composed of 35 students, and the researcher met on the set constraints experienced by students in the subject of colors, including the problem began to search through the following question: - Could employ computer technology (Power point) for the development of technical skills for students of art education in the subject of colors. It also included the chapter one and important goals and assumptions and boundaries and definition of terms either Chapter two guarantees the four sections, the first topic the role of educational technology in the educational process. The second topic of computer source of learning, and the third section of skill and the fourth section colors, while the third quarter included the research methodology and procedures, either Chapter four guarantees the findings, conclusions and recommendations and proposals, then said researcher training program and then sources and references.